Ancient Greco-Roman magic and the agency of victimhood - Eidinow, Esther (Brill, 2017)
Scholarship on ancient Greco-Roman “magic,” over time and place, has largely focused on the role and identity of ritual practitioners, investigating the nature and source of their perceived expertise and often locating it in their linguistic skills. Less attention has been paid to those identified as the targets of magical rituals, who tend to be described as passive recipients of the ritual or the social power of another. In contrast, drawing on the theory of ritual form developed by Robert McCauley and E. Thomas Lawson, alongside the ritualization theories of Catherine Bell, this article argues that victims of magic were also agents of ritual. Focusing on an experience of hostile magic reported by the fourth-century C.E. orator Libanius, it explores how conceptions of magical power were co-created by spell-makers and their so-called victims and should be regarded as relational, that is, as emerging from the interactions of people and groups.